Medicines Wastage at a Tertiary Hospital in Dar Es Salaam Tanzania - Godeliver Anatory Kagashe, Florah Boniface Makenya, Deus Buma (Journal of Applied Pharmaceutical Science, 2014)
Medicines wastage is a problem in health care delivery systems, however the extent of this wastage and associated factors in many health care settings is less known. The objective of this study was to assess medicines wastage and its associated factors in a hospital setting in Dar es Salaam city Tanzania. Specifically to determine major types of medicines wasted and to identify factors contributing towards the wastage. A cross sectional study was carried out at a tertiary hospital, where patient files were analyzed for last admission treatment information for the year 2012. Results show that about 56.3% of medicines prescribed were dispensed to patients. Out of the dispensed medicines, 730 medicines dosages were wasted. Anti-infective medicines wastage was 18.9%, cardiovascular medicines (8.9%) and the other categories was 23.7% of the total medicines dispensed. The factors contributing to medicines wastage were excess (44%), pilferage (26.5%), patient death and change/stop of medicines. Excess supply and pilferage were the major contributing factors. Measures should therefore be taken to mitigate the sources of wastage identified by this study so as to ensure availability of medicines and their rational use in hospital settings.
Keywords: Medicine wastage, pilferage, dispensed medicines, excess supply